CRISPR-mediated TGFBR2 knockout renders human ovarian cancer tumor-infiltrating lymphocytes resistant to TGF-β signaling. Issue 7 (26th July 2022) - Fix, Samantha M; Forget, Marie-Andrée; Sakellariou-Thompson, Donastas; Wang, Yunfei; Griffiths, Tamara M; Lee, Minjung; Haymaker, Cara L; Dominguez, Ana Lucía; Basar, Rafet; Reyes, Christopher; Kumar, Sanjay; Meyer, Larissa A; et al.
Abstract : Background: The correlation between elevated T-cell infiltration and improved survival of ovarian cancer (OvCa) patients suggests that endogenous tumor-infiltrating lymphocytes (TIL) possess some degree of antitumor activity that can be harnessed for OvCa immunotherapy. We previously optimized a protocol for ex vivo OvCa TIL expansion for adoptive cell therapy, which is now being tested in a clinical trial at our institution (NCT03610490 ). Building on this success, we embarked on genetic modification of OvCa TIL to overcome key immunosuppressive factors present in the tumor microenvironment. Here, we present the preclinical optimization of CRISPR/Cas9-mediated knockout of the TGF-β receptor 2 ( TGFBR2 ) in patient-derived OvCa TIL. Methods: OvCa TILs were generated from four patients' tumor samples obtained at surgical resection and subjected to CRISPR/Cas9-mediated knockout of TGFBR2 before undergoing a rapid expansion protocol. TGFBR2 -directed gRNAs were comprehensively evaluated for their TGFBR2 knockout efficiency and off-target activity. Furthermore, the impact of TGFBR2 knockout on TIL expansion, function, and downstream signaling was assayed. Results: TGFBR2 knockout efficiencies ranging from 59±6% to 100%±0% were achieved using 5 gRNAs tested in four independent OvCa TIL samples. TGFBR2 knockout TIL were resistant to immunosuppressive TGF-β signaling as evidenced by a lack of SMAD phosphorylation, a lack of global transcriptional changes in response to TGF-β stimulation, equally strong secretion of proinflammatory cytokines in the presence and absence of TGF-β, and improved cytotoxicity in the presence of TGF-β. CRISPR-modification itself did not alter the ex vivo expansion efficiency, immunophenotype, nor the TCR clonal diversity of OvCa TIL. Importantly for clinical translation, comprehensive analysis of CRISPR off-target effects revealed no evidence of off-target activity for our top two TGFBR2 -targeting gRNAs. Conclusions: CRISPR/Cas9-mediated gene knockout is feasible and efficient in patient-derived OvCa TIL using clinically-scalable methods. We achieved efficient and specific TGFBR2 knockout, yielding an expanded OvCa TIL product that was resistant to the immunosuppressive effects of TGF-β. This study lays the groundwork for clinical translation of CRISPR-modified TIL, providing opportunities for engineering more potent TIL therapies not only for OvCa treatment, but for the treatment of other solid cancers as well.